Tensões discursivas em uma trajetória de estudos sobre a gravidez na adolescência - Alcântara, Kayse Luiza Oliveira de Carvalho (2014)
The present work has the aim the stresses between different ways of seeing and thinking about a given subject; in the specific case of this study, the conflict between discursive formations on teenage pregnancy. The interest in this subject has arisen from the perception of the existence of different speeches about teen pregnancy and the experience of questions in the research process beyond that of existing conflicts put in doubt the nature of truth. This perception was possible from the reflection of several previous studies, whose core were interviews with teenage mothers in 2007, in Recife, for a monographie, focused on the pregnancy in adolescents popular classes. In this study I noticed a conflict as a researcher, subjectivized by a discourse of domination not findind what was claimed, that teenage pregnancy is an experience that generates damage. This speech associates teen pregnancy usually with negative factors for both the mother, and the baby and as a problem that needs attention. Yet another speech, I will call here the resistance, sees the pregnancy based on the reality of life that teenager, so that we can understand the emergence of a pregnancy at that time of life, in all its context. This last speech, seems to reinforce notions of social recognition, desire and autonomy. From the notions of discourse, discursive formations, modes of subjectivity, power / toughness of Michel Foucault this study is to address the research perspective as historically determined by the fact of an era. The speech of the teenagers interviewed shows effects of subjectivity of the two types of speech that make the production of knowledge in theform of research as a field of stress that resonates in ways of thinking and acting of the researcher.